Income Distribution Between Local and Migrant Households in Pheri-Urban of Malang City, East Java Province, Indonesia - Satti Wagistina; Fatiya Rosyida (Sekolah Pascasarjana Universitas Brawijaya, 2019)
This current research aimed at analyzing income distribution between local and migrant households in Lowokwaru District, Malang City. This research occupied a quantitative method by means of a survey. Further, the sample taken for the research comprised 100 households, represented by 50 local and 50 migrant households. The data of income were analyzed by using the Gini ratio, Lorenz curve, and income earning method of World Bank. The results have shown that the income distribution based on log-normal and log-logistic has signified 0.75 – 1.00. Gini ratio index has proved that there is unequal income distribution with the scale from high to perfect level. Meanwhile, Lorenz curve has shown that the highest proportion of income occurs at the high-income interval of the migrant households, and its proportion is shown to decrease along the low income interval of the local households. In other words, the income distribution in Lowokwaru District is far below the diagonal or equity line. In addition, the income earning based on World Bank method has exhibited that as many as 40% of the group with the lowest income has been shown to earn merely 9%. This unequal income distribution, remarking economic discrepancy, has been existent due to different socio-economic characteristics between local and migrant households.